If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + 4x + 15 + -10x = 0 Reorder the terms: 15 + -9x + 4x + -10x = 0 Combine like terms: -9x + 4x = -5x 15 + -5x + -10x = 0 Combine like terms: -5x + -10x = -15x 15 + -15x = 0 Solving 15 + -15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -15x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -15x = 0 + -15 -15x = 0 + -15 Combine like terms: 0 + -15 = -15 -15x = -15 Divide each side by '-15'. x = 1 Simplifying x = 1
| 7u^2-48u-7=0 | | 0.02-0.02(x+2)=-0.04(2-x) | | 6x+6=4x+2 | | 4-(3.5x+2)=x-7 | | 10y-7-6y+9= | | 125x^3-8= | | -10y-7-6y+9= | | 5[15x+25]=950 | | 3x^2-4x-9=0 | | 3x^5-6x^3+11x^2-10=0 | | x+x+9=95 | | 3(x-2)+x+4=2(x-1) | | 2(1-11n)+11=-8(n+1)-7 | | -4x+7=27 | | -2a+40+9a=4a-7a | | x^2*5y^4= | | 4(3y+-1)+13=5y+2 | | 6b=6 | | x^2*5y^2= | | 7[200]+12x=1736 | | 2.5x+2=4x+5 | | 4(3y-10)+13=5y+2 | | x^3-8x-6=0 | | 15x-4=2x+9 | | x+10=x | | 4ax^4-22ax^2+10a= | | 2x+5+7x=32 | | -5x+x+3=-13 | | 14=8x+2y | | -(3+4)=6z-3(3z+2) | | 0=16t^2-96t-112 | | 15-(x-2)= |